Motivational Factors in the Acquisition of Welsh in Poland - Rosiak, Karolina; Hornsby, Michael (Studia Celtica Posnaniensia, 2016)
For some years now, Welsh has been taught as a foreign language outside Wales, most especially in other Celtic countries, central Europe – and Poland. The first courses were established in the Catholic University of Lublin in the 1980s, and this provision has expanded over the years to include a Celtic language specialisation within the Faculty of English at Adam Mickiewicz University in Poznań. Relying at first on teachers from Wales to provide instruction in Welsh, the Centre for Celtic Studies is increasingly producing new, competent speakers/users of Welsh among the Poles. An obvious question to be asked concerns motivational issues – why, on the eastern edges of the European Union, are there people willing to put the effort into learning a language from the far west of Europe, when they have, in some cases, little contact with regular users of Welsh? Through the use of focus group interviews, the present study attempts to discover what motivates Polish students to study Welsh in a context of limited direct contact with the speakers of the language and limited, indirect access to Welsh language and culture.